Analysis Of Human Resource Management Strategies in Enhancing Employee Engagement in Digital Start-Up Companies - Lisbet, Zeanette T.; Hilda Nanda Priyatna; Muliyati; Rahmat Jaya; Andi (International Journal of Economics (IJEC), 2025)
This qualitative study investigates the implementation and effectiveness of human resource management (HRM) strategies in enhancing employee engagement within Indonesian digital start-up companies. The research employed a comprehensive qualitative methodology, including semi-structured interviews with 12 participants across various roles and company sizes within the start-up ecosystem. Data collection involved in-depth interviews, thematic analysis, and examination of HRM practices through multiple lenses. The findings reveal that successful employee engagement in digital start-ups is achieved through strategic implementation of flexible work arrangements, continuous learning programs, digital communication tools, and transparent leadership practices. Key themes emerged around the importance of work-life balance, professional development opportunities, and innovation culture in driving engagement levels. The study demonstrates that start-ups with fully implemented HRM strategies, particularly those emphasizing employee autonomy and career growth, achieve significantly higher engagement scores and job satisfaction rates. Digital transformation in HRM practices, including AI-driven recruitment tools and automated performance management systems, contributes substantially to operational efficiency and employee satisfaction. The research concludes that effective HRM strategies in digital start-ups require a holistic approach that integrates technology adoption with human-centered practices, emphasizing the critical role of leadership engagement and organizational culture in fostering sustained employee commitment